First-principles Study of Structure, Energetic and Infrared Spectrum for IceIh - N, Tsogbadrakh; Sh, Dashpurev (Scientific transaction of the National University of Mongolia. Physics, 2022)
We present the results of density functional based computational study of structure, cohesive energy and IR spectrum of iceIh, and compared with the experimental results. Within the our computational framework the sensitive to calculated structural properties including the zero point vibrations is estimated and shown to be small even though changes in zero point energies account for a significant fraction of the cohesive energy.